Anticancer Effects and Mechanisms of Berberine from Medicinal Herbs: An Update Review - Xiong, Ruo-Gu; Huang, Si-Yu; Wu, Si-Xia; Zhou, Dan-Dan; Yang, Zhi-Jun; Saimaiti, Adila; Zhao, Cai-Ning; Shang, Ao; Zhang, Yun-Jian; Gan, Ren-You; Li, Hua-Bin (Molecules (Basel, Switzerland), 2022)
Cancer has been a serious public health problem. Berberine is a famous natural compound from medicinal herbs and shows many bioactivities, such as antioxidant, anti-inflammatory, antidiabetic, anti-obesity, and antimicrobial activities. In addition, berberine shows anticancer effects on a variety of cancers, such as breast, lung, gastric, liver, colorectal, ovarian, cervical, and prostate cancers. The underlying mechanisms of action include inhibiting cancer cell proliferation, suppressing metastasis, inducing apoptosis, activating autophagy, regulating gut microbiota, and improving the effects of anticancer drugs. This paper summarizes effectiveness and mechanisms of berberine on different cancers and highlights the mechanisms of action. In addition, the nanotechnologies to improve bioavailability of berberine are included. Moreover, the side effects of berberine are also discussed. This paper is helpful for the prevention and treatment of cancers using berberine.